MERAWAT LANSIA DENGAN GANGGUAN MOBILISASI MEMBENTUK NILAI SPIRITUAL DAN KULTURAL ANGGOTA KELUARGA DI SRENGSENG SAWAH JAKARTA SELATAN - Lestari, Ratna; Rekawati, Etty; Wiarsih, Wiwin (Media Ilmu Kesehatan, 2018)
Background: Mobility impairment is a chronic disease that needs long-term care. This condition will change many aspects of eldersâ life that are difficult to adapt. Family members who act as a caregiver are the essential part of eldersâ life. Objective: This study aimed to explore the meaning of caregiving for elders with mobility impairment by family members.Methods: In-depth interviews were conducted with eight family caregivers who were taking care for mobility-impaired elders. In this phenomenological qualitative study, data were then analyzed with content analysis by Colaizzi method. Results: The essence of elderly caregiving for family was to grow both spiritual and cultural values in their lives. Looking for the Lordâs blessing; lifeâs tests; looking for the Lordâs fortune; and Godâs training for patience were included in the spiritual value while the cultural values consisted of child obligation; responsibility; future expectation; role model for children; and filial piety.   Conclusion: Obstacles faced by family caregivers can be overcome by taking the essence of caregiving as part of spiritual and cultural values thus caring can be provided continuously and compassionately. The findings recommended the cultural aspects in caring elderly need to be investigated further using ethnography approach.  Keywords : Cultural Values, Elderly, Family Caregiver, Mobility Impairment, Spiritual Values